PENGARUH KEPATUHAN WAJIB PAJAK DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PPH PASAL 25/29 WAJIB PAJAK BADAN PADA KPP PRATAMA BATANG - Imas Septiyani Hanifah; R. Ery Wibowo Agung S (MAKSIMUM, 2012)
One of the things that influence the most of the acceptance of income tax article 25/29corporate taxpayers is the level of tax compliance, especially in BatangPratama Tax Office. The large amount of income tax revenue of article 25/29 corporate taxpayers nothing to do with the level of tax compliance, ie whether or not the obedient corporate taxpayers in paying taxes. The purpose of this study was to determine the effect of tax compliance and tax collection on income tax receipts article 25/29 corporate taxpayers in the BatangPratamaTax Office period 2008-2012. The survey was conducted at the BatangPratamaTax Office and units of analysis are secondary data from reports of receipts of income tax article 25/29 corporate taxpayers the period 2008-2012. Regression models were used in compliance with the classical assumption test. The data analysis technique used is the technique of multiple linear regression analysis using SPSS version 16.0 The results showed that in the period of 5 (five) years ie 2008 to 2012, the amount of income tax revenue of article 25/29 corporate taxpayers in the BatangPratama Tax Office continued to increase from year to year, tax compliance and collection tax simultaneously and partially significant effect on income tax receipts article 25/29 taxpayers on BatangPratamaTax Office period 2008-2012. Keywords: Taxpayer Compliance, Tax Billing, Tax Receipts Article 25/29, the Taxpayer.